Study on Droplet Entrainment of High-Viscosity Falling Liquid Film - Jun INUMARU; Maromu OHTAKA; Hiroaki WATANABE (Journal of Fluid Science and Technology, 2010)
An experimental study of counter-current annular two-phase flow of high-viscosity liquid and air in a large diameter pipe was carried out to investigate the inception criterion for entrainment of molten slag droplet in an entrained flow coal gasifier. Liquid film thickness was measured using a high-speed camera for 4 types of liquid with various viscosities and surface tensions. It was clearly shown that the measured average wave amplitude had a good correlation with the gas Reynolds number, and that the predicted critical gas velocity for droplet inception using new formula of wave amplitude had a good agreement with the experimental results under the condition of very low fluid Reynolds number( Ref ≤10). The critical Weber number Wec =1.73 was obtained as inception criterion of droplet entrainment.